Profesionalisme Pendidik Dalam Perspektif Islam (Kajian Profesionalisme Guru Dalam PP No 19 Tahun 2017 Tentang Guru dan Dosen) - Santanu Mufti Ratna Wulansari; Elfi Muawanah (The Elementary Journal, 2024)
The background to writing this article is the professionalism of educators from an Islamic perspective which is guided by PP No. 19 of 2017 concerning Teachers and Lecturers. Teacher Competency is the teacher's ability to master learning which includes: planning, implementing and evaluating learning in accordance with their field of expertise. This article aims to describe teacher competence from an Islamic perspective. A professional teacher is a teacher who has special skills and expertise in the field of teaching so that he is able to carry out his duties optimally. Indicators of the achievement of a teacher who is said to be professional include: 1) The teacher has mastered the subject matter he teaches, 2) The teacher has mastered competency standards and basic competencies, 3) The teacher is able to develop learning creatively, 4) The teacher is able to carry out reflective actions, 5) The teacher is able to master information technology in communicating. The following are ways that teachers can improve teacher professional competence, including: 1) Strengthening Teacher Work (PKG), 2) Teacher Working Groups (KKG), 3) Teachers can actively participate in the Republic of Indonesia Teachers Association organization (PGRI).